The Erasmus+ Programme and Sustainable Development Goals—Contribution of Mobility Actions in Higher Education. - Nogueiro, Teresa (2022)
Erasmus+ is an EU programme in the fields of education, training, youth and sport for the period 2014–2021 with a major impact at the international level. These areas are making important contributions to help address socioeconomic changes and the key challenges that Europe will face until the end of the decade as well as to support the implementation of the European policy agenda for growth, jobs, equity and social inclusion. The general objectives of the Erasmus+ Programme are intended to contribute to the overall achievement of the objectives of the Europe 2020 Strategy, among others related to sustainable development. Therefore, the main question is: “To which Sustainable Development Goals (SDG) do the Erasmus+ Programme and the mobility projects for higher education directly contribute to?” The answer to this question will allow us to start filling the knowledge gap at the borderline between SDG and Erasmus+. The purpose of this research is to identify, among the 17 SDGs, those that could be more relevant in the context of mobility projects in higher education within the Erasmus+ Programme and how these projects contribute to these identified SDGs. Through the analysis of the general objective of the Erasmus+ Programme, its most important characteristics and the objectives of Key Action 1 and mobility projects, we can conclude that, from the 2030 Agenda, the most relevant SDGs for the programme and for the action and mobility projects are 4 (quality education), 5 (gender equality) and 8 (decent work and economic growth)